Diagnostic discrepancy in second opinion reviews of primary epithelial neoplasms involving salivary gland: An 11‐year experience from a tertiary referral center focusing on useful pathologic approaches and potential clinical impacts. Issue 8 (24th April 2021) - Xu, Bin; Ghossein, Ronald; Ho, Alan; Viswanathan, Kartik; Khimraj, Anjanie; Saliba, Maelle; Cracchiolo, Jennifer R.; Katabi, Nora
Abstract: Aims: In the era of precision medicine, accurate pathologic diagnoses are crucial for appropriate management. Methods: We herein described the histologic features and clinical impacts of 66 salivary gland epithelial neoplasms in which the diagnosis was altered after expert review. Results: The most common revised diagnosis was that of salivary duct carcinoma (SDC, n = 12), adenoid cystic carcinoma ( n = 12), and myoepithelial carcinoma ( n = 10). The most common initial diagnosis was mucoepidermoid carcinoma ( n = 19) with SDC being the most common revised diagnosis (7/19). Thirteen salivary gland carcinomas were initially diagnosed as benign entities, whereas five benign tumors were initially interpreted as carcinoma. The change in diagnosis was considered to be clinically significant in 65 (97%) cases. Conclusions: Given their rarity, salivary gland neoplasms are prone to diagnostic inaccuracy and discrepancy. A constellation of histologic features and ancillary studies are useful in reaching the correct diagnosis, which can have significant clinical impacts.